COMPARATIVE EVALUATION OF REAL-TIME PCR WITH CONVENTIONAL PCR ASSAY FOR DIAGNOSIS OF BRUCELLOSIS IN RUMINANTS - M. Z. Saleem1; R. Akhtar; A. Aslam; M. I. Rashid; Z. I. Chaudhry; B. A. Shah; R. Ahmed; M. Akmal; G. Murtaza (Journal of Animal and Plant Sciences, 2020)
Brucellosis is zoonotic and highly infectious disease which not only causes the economic losses in ruminants but also infect the humans. In the present study, we compared the molecular techniques of PCR versions and clinical specimens for the diagnosis of brucellosis in ruminants. Blood and serum samples were collected from 692 cattle, 798 buffalo, 471 sheep and 960 goats from two areas; Kasur and Sheikhupura. After serological screening with Rose Bengal antigen, the seropositive serum samples of 73 cattle, 61 buffalo, 91 sheep and 118 goats were subjected to Real-time PCR and Conventional PCR for comparison. Real-time PCR detected significantly (P≤ 0.01) more Brucella abortus (66 cattle, 53 buffalo) and Brucella melitensis (59 sheep, 81 goats) in large and small ruminants, respectively in the serum samples of seropositive ruminants than conventional PCR (45 cattle, 37 buffalo, 34 sheep and 47 goats). The Chi-square analysis confirmed significantly (P≤ 0.01) more detection of B. abortus (66 cattle, 53 buffalo) and B. melitensis (59 sheep, 81 goats) in serum samples specimens of cattle, buffalo and sheep, goats, respectively than their respective blood samples (48 cattle, 39 buffalo, 44 sheep and 63 goats) in seropositive ruminants. It can be concluded that real-time PCR assay is more sensitive and reliable method for the diagnosis of brucellosis, that serum is the optimal specimen for the diagnosis of brucellosis by Real-time PCR.
Keywords: Brucellosis; B. abortus; B. melitensis; Buffalo; Cattle; PCR; RBPT; Molecular diagnosis.